1977
DOI: 10.1161/01.str.8.3.322
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular response to infused 5-hydroxytryptamine in the baboon. Part 1. 5-Hydroxytryptamine infusion.

Abstract: SUMMARY Cerebral blood flow was measured in 17 baboons before and during infusion of S-hydroxytryptamine (5-HT) into the internal carotid artery. The mean values for total cerebral blood flow, grey matter flow, and white matter flow before 5-HT infusion were 40.8, 59.2, and 12.7 ml/min/100 gm of tissue, respectively. There was no significant alteration in total blood flow or flow through grey matter when 5-HT was infused at dosages ranging from 0.5 to 10.0 pg/kg/min. A small but significant decrease in white m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Recent data from our laboratory have shown that migraine with and without aura differ in platelet catecholamine and serotonin balance between attacks (19) and in catecholamine-related, event-related slow potentials (20,21). Together with the present evidence that oestradiol levels differ in migraine with and without aura, these findings are compatible with our previous postulate (22) that oestrogens may modulate the vascular or primary neurophysiological changes associated with migraine via an interaction with noradrenergic and serotonergic function (9)(10)(11)(12)(13)(22)(23)(24)(25). They also support the concept that, via whatever pathophysiological mechanism, variation in oestradiol levels may be an important common factor that underlies the differing clinical expressions of the migraine disorder.…”
Section: Discussionsupporting
confidence: 90%
“…Recent data from our laboratory have shown that migraine with and without aura differ in platelet catecholamine and serotonin balance between attacks (19) and in catecholamine-related, event-related slow potentials (20,21). Together with the present evidence that oestradiol levels differ in migraine with and without aura, these findings are compatible with our previous postulate (22) that oestrogens may modulate the vascular or primary neurophysiological changes associated with migraine via an interaction with noradrenergic and serotonergic function (9)(10)(11)(12)(13)(22)(23)(24)(25). They also support the concept that, via whatever pathophysiological mechanism, variation in oestradiol levels may be an important common factor that underlies the differing clinical expressions of the migraine disorder.…”
Section: Discussionsupporting
confidence: 90%
“…In cats, Reivich et al u reported rCBF values of 109 ± 4 ml/lOOg brain/min for the sensory-motor cortex and 81 ± 5 ml/lOOg brain/min for association cortex. In gerbils Van Uitert et al 18 reported rCBF values of 102 ± 4 ml/lOOg brain/min for the cerebral hemispheres. Hemispheric Fg values during pentobarbital anesthesia in the present studies (57.2 ± 9.3 ml/lOOg brain/min) are also in good agreement with reported values of 52.0 ± 1 .…”
Section: Painless Measurements Of Rcbf In the Baboonmentioning
confidence: 99%